Mass Phenomenon in Finding Viral Information on Instagram Social Media - Ratu Aulia Bernatta (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2020)
AbstractThe phenomenon of the mass in searching for viral information on social media (Instagram) is a reflection that the internet, especially social media today has become the opiate of the masses in their lives. The advantages offered and presented by social media in providing information with a faster and more accurate time become a reference for the masses in choosing media to seek and obtain information and communication in their lives. This study uses descriptive qualitative research methods, this is because the data that the researcher wants to present is in the form of stories from the speakers about experiences, opinions, knowledge. The theory used is Hypodermic Needle Theory which means that what is presented in the mass media (newspapers, television and online) directly or strongly gives a stimulus to the audience. In addition, this study also uses the Phenomenology approach, which in this study will examine the mass phenomenon in finding viral information on social media.